Histamine‐2 (H2) antagonists can be safely removed from standard paclitaxel premedication regimens. Issue 9 (8th May 2022) - Foreman, Emma; Polwart, Calum; Walker, Andrew; Chambers, Pinkie
Abstract : Aims: The aim of this study is to investigate the rates of hypersensitivity reactions (HSRs) in patients receiving paclitaxel chemotherapy, with and without a histamine‐2 (H2 ) antagonists. Method: This prospective, multi‐centre, cohort study compared patients receiving paclitaxel treated with premedication regimens containing chlorphenamine, dexamethasone and an H2 antagonist vs patients treated without an H2 antagonist. Rates of HSRs were described and logistic multivariable regression was used to investigate any associations with H2 antagonist treatment, adjusting for confounding variables. Results: A total of 1043 individuals were included in the study; of these, 638 (61%) patients received an H2 antagonist and 405 (49%) were not given an H2 antagonist. Incidence of HSR in the cohort treated with H2 antagonists was 11.31% ( n  = 70) vs 9.86% ( n  = 41) in the cohort without. There was no statistically significant difference between the rates of HSR observed in those receiving and not receiving an H2 antagonist (odds ratio 1.04, 95% CI 0.65, 1.66, P  = .9). Conclusions: Results presented within the study are consistent with other recently published evidence to suggest that H2 antagonists do not confer any advantage as part of premedication regimens in reducing the incidence of HSR in patients treated with paclitaxel.